Ways of shaping the Lean culture in enterprises in Poland - Walentynowicz, Piotr Sergiusz; Omiotek, Pamela (Zielona Góra: Faculty of Economics and Management Press)
As we know from many publications, it is worth using Lean Management in modern enterprises. On the other hand, as scientists and practitioners emphasise, developing an appropriate organisational culture is necessary to obtain the proper results as part of Lean Management. Therefore, in parallel with the organisational changes related to implementing the Lean concept in the enterprise, various activities should be carried out to change the organisational culture into a culture favourable to Lean.
Keywords: lean management; results of empirical research; towards Lean culture; methods of changing organizational culture; methods of changing; organizational culture